Durability of crosslinked polydimethylsyloxanes: the case of composite insulators - Delor-Jestin, Florence; Tomer, Namrata S.; Singh, Raj Pal; Lacoste, Jacques (Science and Technology of Advanced Materials, 2008)
Most applications of silicones are linked to their hydrophobic properties and (or) their high resistance to ageing (e. g. thermal ageing and photoageing). However, when placed in extreme environments, these materials can fail as in the case of epoxy/fiber glass composite powerlines insulators, where crosslinked polymethylsyloxanes (PDMSs) are used as the protective envelope (housing) of the insulator. We report on the behavior of both pure/noncrosslinked PDMSs and typical formulations used in industrial insulators, i.e. containing peroxide crosslinked PDMS, alumina trioxide hydrated (ATH) and silica. Special attention is paid on both (i) the sources of potential degradation and (ii) the best analytical methods that can be applied to the study of very complex formulations. (i) Aside from conventional types of ageing such as photo-ageing and thermal, hydrolytic, and service life ageings, treatments with acidic vapors, plasma and ozone possibly generating species from the reaction of a high electric field with air were also performed, which allowed to accelerate electrical and out-door ageings and to obtain differently aged materials. (ii) Aside from conventional analytical methods of polymer degradation such as FTIR/ATR spectroscopy and SEC, TG, hardness measurements, more specific methods like photo/DSC, TG/IR, thermoporosimetry, resistivity and density measurements were also performed to characterize the chemical and physical evolutions of polymer materials. In particular, it was found that treatment with nitric acid vapor has detrimental effects on the properties of both fire retardants (e. g. ATH) and PDMSs, affecting the hardness and resistivity of the formulated material.
International Conference on Magneto-Science, Hiroshima, JAPAN, NOV, 2007
Keywords: composite insulators; durability; PDMS; post-crosslinking; silicone

3D polyaniline porous layer anchored pillared graphene sheets: enhanced interface joined with high conductivity for better charge storage applications - Sekar, Pandiaraj; Anothumakkool, Bihag; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Here, we report synthesis of a 3-dimensional (3D) porous polyaniline (PANI) anchored on pillared graphene (G-PANI-PA) as an efficient charge storage material for supercapacitor applications. Benzoic acid (BA) anchored graphene, having spatially separated graphene layers (G-Bz-COOH), was used as a structure controlling support whereas 3D PANI growth has been achieved by a simple chemical oxidation of aniline in the presence of phytic acid (PA). The BA groups on G-Bz-COOH play a critical role in preventing the restacking of graphene to achieve a high surface area of 472 m(2)/g compared to reduced graphene oxide (RGO, 290 m(2)/g). The carboxylic acid (-COOH) group controls the rate of polymerization to achieve a compact polymer structure with micropores whereas the chelating nature of PA plays a crucial role to achieve the 3D growth pattern of PANI. This type of controlled interplay helps G-PANI-PA to achieve a high conductivity of 3.74 S/cm all the while maintaining a high surface area of 330 m(2)/g compared to PANI-PA (0.4 S/cm and 60 m(2)/g). G-PANI-PA thus conceives the characteristics required for facile charge mobility during fast charge-discharge cycles, which results in a high specific capacitance of 652 F/g for the composite. Owing to the high surface area along with high conductivity, G-PANI-PA displays a stable specific capacitance of 547 F/g even with a high mass loading of 3 mg/cm(2), an enhanced areal capacitance of 1.52 F/cm(2), and a volumetric capacitance of 122 F/cm(3). The reduced charge-transfer resistance (RCT) of 0.67 O displayed by G-PANI-PA compared to pure PANI (0.79 O) stands out as valid evidence of the improved charge mobility achieved by the system by growing the 3D PANI layer along the spatially separated layers of the graphene sheets. The low RCT helps the system to display capacitance retention as high as 65% even under a high current dragging condition of 10 A/g. High charge/discharge rates and good cycling stability are the other highlights of the supercapacitor system derived from this composite material.
Keywords: durability; ionic accessibility; phytic acid; pillaring; polyaniline; restacking

Tweaking palladium electronic structure to attain oxygen reduction activity superior to platinum/C - Sarma, Saurav Ch.; Kaja, Sai Manoj; Mishra, Vidyanshu; Vinod, Chathakudath Prabhakaran; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
Enhancing oxygen reduction (ORR) activity through alloying is crucial to improve the performance of a fuel-cell catalysts. In this work, we have studied the alloying effects of 4f rare-earth (RE) metals with palladium. The modified catalyst exhibits better activity (E-onset = 1 V and E-1/2 = 0.88 V) and higher selectivity toward H2O (similar to 97%) compared to the state-of-the-art catalysts due to complete dissociation of O-2. Hirshfeld charge analysis and 2D-electron localization function reveal improved adsorbate-adsorbent interaction on the catalyst surface. This work paves a strategy to design highly selective non-Pt-based catalysts for the ORR by controlling electronic structures and surface oxide formation.
Keywords: d-band center; DFT calculation; durability; EuPd; oxygen reduction reaction; YbPd